Using social media for patient and public involvement and engagement in health research: The process and impact of a closed Facebook group. (22nd September 2022) - Fedorowicz, Sophia; Riley, Victoria; Cowap, Lisa; Ellis, Naomi J.; Chambers, Ruth; Grogan, Sarah; Crone, Diane; Cottrell, Elizabeth; Clark‐Carter, David; Roberts, Lesley; Gidlow, Christopher J.
Abstract: Background: As part of a multifaceted approach to patient and public involvement and engagement (PPIE), alongside traditional methods, a closed Facebook group was established to facilitate PPIE feedback on various aspects of a project that used video‐recording to examine risk communication in NHS Health Checks between June 2017 and July 2019. Objective: To explore the process and impact of conducting PPIE through a closed Facebook group and to identify the associated benefits and challenges. Methods: Supported by reflections and information from project meetings used to document how this engagement informed the project, we describe the creation and maintenance of the Facebook Group and how feedback from the group members was obtained. Facebook data were used to investigate levels and types of engagement in the closed Facebook group. We reflect on the challenges of using this method of engaging the public in health research. Results: A total of 289 people joined the 'Risk Communication of Cardiovascular disease in NHS Health Checks' PPIE closed Facebook group. They provided feedback, which was used to inform aspects of the study, including participant‐facing documents, recruitment, camera position and how the methodology being used (video‐recorded Health Checks and follow‐up interviews) would be received by the public. Discussion: Using a closed Facebook group to facilitate PPIE offered a flexible approach for both researchers and participants, enabled a more inclusive method to PPIE (compared with traditional methods) and allowed rapid feedback. Challenges included maintaining the group, which was more labour intensive than anticipated and managing members' expectations. Suggestions for best practice include clear communication about the purpose of the group, assigning a group co‐ordinator to be the main point of contact for the group, and a research team who can dedicate the time necessary to maintain the group. Conclusion: The use of a closed Facebook group can facilitate effective PPIE. Its flexibility can be beneficial for researchers, patients and public who wish to engage in the research process. Dedicated time for sustained group engagement is important. Patient or Public Contribution: Patient representatives were engaged with the development of the research described in this paper and a patient representative reviewed the manuscript.